Cell signalling-mediating insulin increase of mRNA expression for cationic amino acid transporters-1 and -2 and membrane hyperpolarization in human umbilical vein endothelial cells - Gonz lez, Marcelo; Flores, Carlos; Pearson, JeremyD; Casanello, Paola; Sobrevia, Luis (Pflügers Archiv, 2004)
Insulin induces vasodilatation in human subjects and increases L-arginine transport and NO synthesis in human umbilical vein endothelial cells (HUVEC). Cell signalling events associated with insulin effects on activity and mRNA expression of the human cationic amino acid transporters 1 (hCAT-1) and 2B (hCAT-2B) are unknown. L-arginine transport and eNOS activity were determined in HUVEC exposed to insulin. mRNA levels for hCAT-1, hCAT-2B and eNOS were quantitated by real time RT-PCR and endothelial NO synthase (eNOS) protein was identified by Western blot analysis. Intracellular Ca2+, L-arginine and L-citrulline levels, L-[3H]citrulline formation from L-[(3)H]arginine, cGMP formation, nitrite level, ATP release and membrane potential were determined. Insulin increased L-arginine transport and the mRNA levels for hCAT-1 and hCAT-2B and eNOS expression and activity. Insulin also induced membrane hyperpolarization and increased intracellular Ca2+, L-[3H]citrulline, cGMP and nitrite formation. Insulin-mediated stimulation of the L-arginine/NO pathway is thus associated with increased hCAT-1 and hCAT-2B mRNA, and eNOS expression, via mechanisms involving membrane hyperpolarization, mitogen-activated protein kinases p42 and p44, phosphatidylinositol 3-kinase, NO and protein kinase C. We have characterized a cell signalling pathway by which hyperinsulinaemia could lead to vasodilatation in human subjects, and which could have implications in patients in whom plasma insulin levels are altered, such as in diabetes mellitus.